Lobbying Activity on International Accounting Standard: An examination of lobbying behaviour on macro hedging treatment - Yu, Xiang (2006)
Lobbying activity has aroused academic interest for a long time and this paper studied lobbying activity on international accounting standards. The main method used in the study was one of the qualitative research methods: context analysis. The paper examined 118 comment letters to the Exposure Draft: Fair Value Hedge Accounting for a Portfolio Hedge of Interest issued by IASB on 21 August, 2003. The main research question was to observe how interested parties lobbied the Board and how the Board made corresponding response. The findings of the investigation showed that IASB quite insisted on its original decision instead of being influenced by lobbying behaviour easily. However, this result contradicted with the conclusion of literature review which stated that standard-setting body usually would give up or make compromise with lobbyists. Therefore, more researches on more international standards need to be conduct to get a more comprehensive and objective picture on the subject.